THE DECONSTRUCTION AND RECONSTRUCTION OF GLOBAL ENVIRONMENTAL GOVERNANCE: CASE STUDY OF PEAT RESTORATION AGENCY - Verdinand Robertua (Kajian Asia Pasifik, 2018)
Forest fires in 2015 in Indonesia has destructed severely Indonesian peat and forest. Peat Restoration Agency was established to restore degraded peat and protect the remaining intact peat. The problem is that Indonesia has complex political administration and isolated peatland. Meanwhile there is significant wave of states retreat from global environmental governance. This research would like assess the performance of global environmental governance using the case study of Peat Restoration Agency. This research is a qualitative study with the emphasis of conceptual and theoretical development. Environmental Studies of English School and global environmental governance are the theoretical and conceptual focus respectively. Primary data is collected through semi-structured interview with head of Peat Restoration Agency, environmental activists in WWF Indonesia, WALHI and Greenpeace Indonesia. There are two key finding in this research. Firstly, the absence of immutability thesis is essential for expanding pluralism in Environmental Studies of English School (ESES). Secondly, deconstruction and reconstruction of global environmental governance has implication toward the reconstruction of environmental diplomacy. Keywords: Peat Restoration Agency, Environmental Studies of English School, environmental diplomacy, Global Environmental Governance, peatland Abstrak Kebakaran hutan yang terjadi pada tahun 2015 telah menghancurkan lahan gambut yang sangat luas. Merespons kerusakan tersebut, Badan Restorasi Gambut dibentuk dengan tujuan memulihkan lahan gambut yang rusak dan melindungi lahan gambut yang utuh. Inisiatif ini menghadapi masalah dimana Indonesia memiliki sistem pemerintahan yang kompleks dan lahan gambut yang sulit diakses dari pusat pemerintahan. Tata kelola lingkungan global juga menghadapi masalah dimana negara anggotanya memilih untuk bersikap pasif. Penelitian ini mengevaluasi kinerja dari tata kelola lingkungan global melalui studi kasus Badan Restorasi Gambut. Penelitian ini adalah penelitian kualitatif dengan tujuan penelitian yaitu pengembangan konsep tata kelola lingkungan global dan teori Environmental Studies of English School. Data primer diperoleh melalui serangkaian wawancara dengan kepala Badan Restorasi Gambut, aktivis lingkungan WWF Indonesia, WALHI dan Greenpeace Indonesia Terdapat dua kesimpulan yang diperoleh penelitian ini. Pertama, penghapusan immutability thesis merupakan bagian dari pengembangan pluralisme dalam Environmental Studies of English School. Kedua, dekonstruksi dan rekonstruksi tata kelola lingkungan global berimplikasi terhadap rekonstruksi diplomasi lingkungan. Kata kunci: Badan Restorasi Gambut, Environmental Studies of English School, diplomasi lingkungan, tata kelola lingkungan global, lahan gambut